Characterization of pathogenic microbiome on removable prostheses with different levels of cleanliness using 2bRAD-M metagenomic sequencing - Tong Wah Lim; Shi Huang; Yuesong Jiang; Yufeng Zhang; Michael Francis Burrow; Colman McGrath (Journal of Oral Microbiology)
Background The microbiomes on the surface of unclean removable prostheses are complex and yet largely underexplored using metagenomic sequencing technology.Objectives To characterize the microbiome of removable prostheses with different levels of cleanliness using Type IIB Restriction-site Associated DNA for Microbiome (2bRAD-M) sequencing and compare the Microbial Index of Pathogenic Bacteria (MIP) between clean and unclean prostheses.Materials and Methods Ninety-seven removable prostheses were classified into ‘clean’ and ‘unclean’ groups. All prosthesis plaque samples underwent 2bRAD metagenomic sequencing to characterize the species-resolved microbial composition. MIPs for clean and unclean prostheses were calculated based on the sum of the relative abundance of pathogenic bacteria in a microbiome using a reference database that contains opportunistic pathogenic bacteria and disease-associated information.Results Beta diversity analyses based on Jaccard qualitative and Bray-Curtis quantitative distance matrices identified significant differences between the two groups (p < 0.05). There was a significant enrichment of many pathogenic bacteria in the unclean prosthesis group. The MIP for unclean prostheses (0.47 ± 0.25) was significantly higher than for clean prostheses (0.37 ± 0.29), p = 0.029.Conclusions The microbial community of plaque samples from ‘unclean’ prostheses demonstrated compositional differences compared with ‘clean’ prostheses. In addition, the pathogenic microbiome in the ‘unclean’ versus ‘clean’ group differed.